Optimal fibular tunnel direction for anterior talofibular ligament reconstruction: 45 degrees outperforms 30 and 60 degrees - Liu, Cheng-Xiao; Zhang, Zheng-Zheng; Wang, Jing-Song; Luo, Xi-Yuan; Liu, Tian-Yu; Ma, Yu-Fan; Deng, Xing-Hao; Zhou, Yun-Feng; Xu, Da-Zheng; Li, Wei-Ping; Wang, Peng; Song, Bin (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2023)
Purpose There is currently no consensus on the optimal drilling direction of the fibular bone tunnel for anterior talofibular ligament (ATFL) reconstruction, and few studies have investigated the potential injury to the peroneus longus and brevis tendons and the possibility of fibular fractures during the drilling process. The aim of this study was to assess the potential risk of drilling the tunnel from different directions and determine the most appropriate tunnel direction. The hypothesis was that drilling the tunnel in the 45-degree direction would be the safest and most suitable for the fibular tunnel. Methods Forty-eight fibular tunnels were drilled on fresh ankle specimens using a K-wire guide and a 5.0 mm hollow drill. Three tunnel orientations were created, parallel to the sagittal plane of the long axis of the fibula and angled 30°, 45°, and 60° to the coronal plane. The length of the fibular tunnel and the distances from the outlet of the K-wire to the peroneus longus and brevis tendons were measured. The occurrence of a fibula fracture was also observed. Results The lengths of the bone tunnels in the three groups were 32.9 ± 6.1 mm (30°), 27.2 ± 4.4 mm (45°) and 23.6 ± 4.0 mm (60°). The length of the tunnel drilled at 30° was the longest when compared with that of the tunnels drilled at 45° and 60° (all p values < 0.05). The distances from the outlet of the K-wire to the peroneus longus tendon were 3.0 ± 3.8 mm (30°), 3.8 ± 3.2 mm (45°) and 5.3 ± 1.8 mm (60°), and the distances to the peroneus brevis tendon were 4.2 ± 4.0 mm (30°), 6.1 ± 3.8 mm (45°), 7.9 ± 3.5 mm (60°). In terms of protecting the peroneus longus and brevis tendons, drilling in the 60° direction was better than drilling in the 30° and 45° directions (all p values < 0.05). The risk of injury to the peroneal longus and brevis tendons was 62.5% (30°), 31.3% (45°), and 0% (60°). Although no fibular fractures were observed in any of the three directions, drilling the bone tunnel in the 60° direction disrupted the lateral cortex of the fibula. Conclusion This study shows that drilling the tunnel in the 45° direction is less likely to cause injury to the peroneus longus and brevis tendons, while ensuring that the tunnel has a sufficient length and avoiding fracturing the distal fibula. Drilling a fibular bone tunnel in a 45° direction is safer and recommended for ATFL reconstruction.